Epithelial transport of anthelmintic ivermectin in a novel model of isolated proximal kidney tubules - Fricker, Gert (Pharmaceutical research, 1999)
Purpose. The mechanism of excretion of the anthelmintic drug ivermectin was investigated in a novel experimental model of functionally intact proximal tubules isolated from a teleost fish (Fundulus heteroclitus).Methods. Secretion into the lumens of freshly isolated proximal tubules was studied by means of confocal laser scanning microscopy and digital image analysis using ivermectin and fluorescent labelled ivermectin (BODIPY-ivermectin; BI) as substrates.Results. The tubular cells rapidly accumulated BI from the medium and attained steady state within 25 minutes. Luminal fluorescence in the steady state was 5-7 times higher as compared to intracellular fluorescence. The secretion of BI into the tubular lumens was inhibited in a dose dependent manner by unlabelled ivermectin and inhibitors of the renal excretory membrane pump p-glycoprotein, namely SDZ PSC-833 and verapamil, but not by leukotriene C4, a substrate of the renal export protein mrp2. Accumulation inside the tubular cells was not affected by the added inhibitors. Ivermectin inhibited the renal secretion of the fluorescent cyclosporin derivative NBDL-CS, a substrate of p-glycoprotein, but not the secretion of the mrp2-substrate fluorescein-methotrexate, nor the secretion of fluorescein, a substrate of the classical renal organic anion transporter.Conclusions. The data are consistent with BI and ivermectin interacting in teleost kidney tubules exclusively with p-glycoprotein, but not with one of the other known excretory transport systems. In addition, the studies demonstrate that freshly isolated functionally intact kidney tubules from killifish are a useful tool to differentiate the substrate specificity of renal transport systems with respect to drug elimination.
Gesehen am 26.04.2017